UNC13B Promote Arsenic Trioxide Resistance in Chronic Lymphoid Leukemia Through Mitochondria Quality Control - Wang, Xiao-Bo; Yuan, Li-Hua; Yan, Le-Ping; Ye, Yong-Bin; Lu, Bo; Xu, Xiaojun (Frontiers in Oncology, 2022)
In clinical practice, arsenic trioxide can be used to treat a subset of R/R CML patients, but resistance tends to reappear quickly. We designed an experiment to study arsenic trioxide resistance in K-562 cells. Previously, we identified the UNC13B gene as potentially responsible for arsenic trioxide resistance in K-562 cells via gene chip screening followed by high-content screening. We aimed to investigate the role and mechanism of the UNC13B gene in K-562 cells, an arsenic trioxide-resistant chronic myeloid leukemia cell line. In vitro lentiviral vector-mediated UNC13B siRNA transfection was performed on K-562 cells. The roles of UNC13B in cell proliferation, apoptosis and cell cycle pathways, and colony formation were analyzed by CCK-8 assay, fluorescence-activated cell sorting, and soft agar culture, respectively. Gene chip screening was used to define the possible downstream pathways of UNC13B. Western blot was performed to further validate the possible genes mediated by UNC13B for arsenic trioxide resistance in patients with chronic myeloid leukemia. UNC13B downregulation significantly inhibited growth, promoted apoptosis, decreased colony formation, reduced the duration of the G1 phase, and increased the duration of the S phase of K-562 cells. Western blot results confirmed that UNC13B may modulate the apoptosis and proliferation of arsenic trioxide-resistant chronic myeloid leukemia cells through the mediation of MAP3K7, CDK4, and PINK1. UNC13B is a potential therapeutic target for patients with arsenic trioxide-resistant chronic myeloid leukemia.